Kinerja dan Revitalisasi Birokrasi Publik - Monang Sitorus (Jurnal Administrasi Publik, 2008)
The state is not only the answer of human "fitrah" in the collective life but also is a social contract based on equity. The main pillar that is needed in implementing the social contract is strong bureaucracy. Bureaucracy performance will face full turbulence and uncertainty of threats. Therefore, bureaucracy must be revitalize in accordance with the developmental period. Bureaucratic Reform Committee (BRC) is one of the strategies to revitalize the bureaucratic machine in order to remain exist. The revitalization can be conducted in an incremental and radical way, that is started from official/staff recruitment and then they are trained through the Center of Integrated Apparatur Training. All these can be undertaken if supported by all parties.Keyword: bureaucracy, revitalization, performance